Integrating theory and practice in social work education - Watson, Florence, 1958- (Jessica Kingsley Publishers, 2002)
This clear and instructive text gives practical advice on how to write better essays or assessments and give better presentations within social work. It shows how practitioners and students can apply theoretical considerations to practical social work and how they can articulate this connection in written or oral reports, both in pre-qualification and for professional development post-qualification. The authors, experienced teachers and researchers in social work education, explain how to go about gathering evidence from fieldwork and practice placements and how to prepare and plan an assignment or project. They give guidance on incorporating ethical considerations and theoretical developments, applying law and policy, and developing all these aspects in reflection, analysis and evaluation of practice.
Keywords: Social work education -- Great Britain.; Practicums -- Great Britain.; Academic writing.; Report writing.; Service social -- Étude et enseignement -- Grande-Bretagne.; Stages -- Grande-Bretagne.; Écriture savante -- Grande-Bretagne.; Rapports -- Rédaction -- Grande-Bretagne.; Écriture savante.; Rapports -- Rédaction.; SOCIAL SCIENCE -- Social Work.; Academic writing; Practicums; Report writing; Social work education; Great Britain; Samfundsvidenskab -- Sociologi.